Race and Disability: From Analogy to Intersectionality. Issue 2 (April 2019) - Frederick, Angela; Shifrer, Dara
Sociologists are using intersectional lenses to examine an increasingly wider range of processes and identities, yet the intersection of race and disability remains a particularly neglected area in sociology. Marking an important step toward filling this gap, the authors interrogate how race and disability have been deployed as analogy in both disability rights activism and in critical race discourse. The authors argue that the "minority model" framework of disability rights has been racialized in ways that center the experiences of white, middle-class disabled Americans, even as this framework leans heavily upon analogic work likening ableism to racial oppression. Conversely, the authors examine the use of disability as metaphor in racial justice discourse, interrogating the historic linking of race and disability that gave rise to these language patterns. The authors argue that this analogic work has marginalized the experiences of disabled people of color and has masked the processes by which whiteness and able-bodiedness have been privileged in these respective movements. Finally, the authors argue that centering the positionality of disabled people of color demands not analogy but intersectional analyses that illuminate how racism and ableism intertwine and interact to generate unique forms of inequality and resistance.